Novel HexA splice site mutations in a patient with late atypical onset Tay-Sachs disease: importance of combined NGS and biochemical analysis - Bilyalova, Alina; Shagimardanova, Elena; Bilyalov, Airat; Zaripova, Marina; Shigapova, Leyla; Gazizova, Guzel; Mazin, Pavel; Tatiana, Bukina; Gusev, Oleg (Frontiers in Neurology, 2024)
Tay-Sachs disease (TSD) is a rare genetic disorder with diverse clinical manifestations, often leading to underdiagnosis due to symptom similarities with other neurological conditions. We aimed to uncover the genetic underpinnings of late-onset TSD in a 27-year-old patient with progressive neurological symptoms. Whole exome sequencing revealed two hexA gene mutations linked to TSD: a known c.805G>A (p.Gly269Ser) variant and a novel splice site mutation, c.346+2dupT. Clinical assessments, genetic analysis, and functional investigations, including RNA sequencing and enzymatic activity assays, confirmed the novel mutation's pathogenicity. Our findings highlight the efficacy of advanced genomic technologies in diagnosing intricate genetic disorders and emphasize the significance of functional validation for confirming mutation effects. Identifying compound heterozygous mutations in the hexA gene sheds light on Mendelian inheritance patterns. This case underscores the diagnostic challenges posed by overlapping clinical phenotypes and stresses the need for heightened genetic awareness among clinicians. Accurate TSD diagnosis profoundly impacts patients and families, enabling informed genetic counseling and guiding clinical management choices. While treatment options are limited, timely and accurate diagnosis holds promise for future research and interventions. This study showcases the value of a multidisciplinary approach in unraveling the molecular basis of complex genetic diseases and informing clinical decisions. удалено: 1, 34 отформатировано: надстрочные, выделение цветом отформатировано: Шрифт: курсив отформатировано: выделение цветом удалено: gangliosidoses 78 отформатировано: выделение цветом удалено: The adult-onset TSD has strong varyation of age of the 79 disease debut and a heterogeneity of clinical manifestation, resulting